115k views
2 votes
2y-10=6x
plz help me

User Skatephone
by
5.8k points

1 Answer

4 votes

Answer: simplifying

Step-by-step explanation:

2y + -10 = 6x

Reorder the terms:

-10 + 2y = 6x

Solving

-10 + 2y = 6x

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '10' to each side of the equation.

-10 + 10 + 2y = 10 + 6x

Combine like terms: -10 + 10 = 0

0 + 2y = 10 + 6x

2y = 10 + 6x

Divide each side by '2'.

y = 5 + 3x

Simplifying

y = 5 + 3x

Explanation:

your well come...

User Sergey Passichenko
by
6.4k points